Der p 1 facilitates transepithelial allergen delivery by disruption of tight junctions - Hong Wan; Helen L. Winton; Christian Soeller; Euan R. Tovey; Dieter C. Gruenert; Philip J. Thompson; Geoffrey A. Stewart; Graham W. Taylor; David R. Garrod; Mark B. Cannell; Clive Robinson (The Journal of Clinical Investigation, 1999)
House dust mite (HDM) allergens are important factors in the increasing prevalence of asthma. The lung epithelium forms a barrier that allergens must cross before they can cause sensitization. However, the mechanisms involved are unknown. Here we show that the cysteine proteinase allergen Der p 1 from fecal pellets of the HDM Dermatophagoides pteronyssinus causes disruption of intercellular tight junctions (TJs), which are the principal components of the epithelial paracellular permeability barrier. In confluent airway epithelial cells, Der p 1 led to cleavage of the TJ adhesion protein occludin. Cleavage was attenuated by antipain, but not by inhibitors of serine, aspartic, or matrix metalloproteinases. Putative Der p 1 cleavage sites were found in peptides from an extracellular domain of occludin and in the TJ adhesion protein claudin-1. TJ breakdown nonspecifically increased epithelial permeability, allowing Der p 1 to cross the epithelial barrier. Thus, transepithelial movement of Der p 1 to dendritic antigen-presenting cells via the paracellular pathway may be promoted by the allergen’s own proteolytic activity. These results suggest that opening of TJs by environmental proteinases may be the initial step in the development of asthma to a variety of allergens.